PENGARUH DEEP BACK MASSAGE TERHADAP PENURUNAN NYERI PERSALINAN - Liva Maita (Universitas Nahdlatul Ulama Surabaya, 2016)
Labor pain occurs because of the contraction, if not resolved quickly can cause death to the mother and the baby, because it causes the flow of blood and oxygen to the placenta disturbed. Various attempts to reduce labor pain, no pharmacological or nonpharmacological one with Deep back massage. The purpose of this study is to determine the effectiveness of Deep Back Massage to decrease maternal pain when I. This type of quantitative research design Quasi Experiment. The population is all women giving birth in February of BPM Khairani s / d April 2016 as many as 21 people. Bivariate data analysis using t test dependent, with Mc. Nemar test. The result showed the majority of women who experience pain 6-10 as many as 13 people (61.9%) experienced mild pain relief 0-4 of 4 people. Bivariate data obtained no significant effect between Deep Back Massage to decrease labor pain with a p value of 0.004. Deep Back Massage techniques should have been taught during the third trimester of pregnancy during pregnancy exercise class. Keywords: Deep Back Massage; Painful Childbirth